KESADARAN HUKUM KONSUMEN TERKAIT PENANDAAN PADA PRODUK KOSMETIK YANG DIPRODUKSI OLEH KLINIK KECANTIKAN - Astanti, Dilla Nurfiana (Universitas Negeri Surabaya, 2020)
Cosmetic products produced by beauty clinics according to Regulation of the Head of the BPOM No. 19 of 2015 on Cosmetic Technical Requirements must contain a minimum marking in the form of complete, objective, and not misleading information. The existence of cosmetic products that attached to the skin if they do not contain markings, it will endanger the health and safety of consumers. Marking is includes in the consumer's right to information as stipulated in Law of the Republic of Indonesia Number 8 of 1999 on Consumer Protection (UUPK) which has a correlation with the business actor's obligation to include true, clear and honest information. Increased awareness, ability, and independence of consumers to protect themselves is needed if the business actor fails to carry out its obligations. This study aims to analyze consumer legal awareness related to marking on cosmetic products produced by beauty clinics. The research method used is empirical juridical data collection techniques through interviews, observation, and documentation. The results showed that consumer legal awareness was related to the marking of cosmetic products produced by beauty clinics at very low levels. The low awareness of consumer law is influenced by several factors which include the level of education, age, lack of awareness of the obligation of labeling by business actors, and consumers have never received information (socialization) related to the marking from the Central POM in SurabayaKeywords: Consumer Law Awareness, Right to Information, Cosmetic Marking